ANALISIS KERUSAKAN LAHAN PEMUKIMAN PADA KAWASAN BERDAMPAK LAHAR DINGIN GUNUNG MARAPI KABUPATEN TANAH DATAR SUMATERA BARAT - Yanto, Andri; Veni, Veni; Rahayu, Intan Dwi; Febrianto, Hary; Simponi, Maijem; Afrianto, Nanda (Jurnal Manajemen Pendidikan, 2024)
Mount Merapi, Tanah Datar Regency, West Sumatra is one of the active volcanoes in Indonesia, especially on the island of Sumatra. One of the dangers posed by active volcanoes after an eruption is cold lava. Merapi Volcano has many rivers that originate at the top of Merapi, such as Bukik Batabuah, Pua River, several rivers in Batipuah District. Cold lava is a secondary disaster that cannot be underestimated because the impact it causes is just as big as a primary disaster if it is not handled properly. This research was carried out by direct observation of the disaster area, namely the foot of Mount Marapi with purposive sampling. Therefore, it is necessary to map the areas affected by cold lava. The area affected by the lava flow was modeled and simulated by means of spatial analysis using the parameters of the volume of the lava flow, the starting point of the river, and the slope of the slope, with the aim of finding out how fast the lava flows towards the settlement. From the aftermath of the Mount Marapi disaster, the distribution of areas that have the potential for pyroclastic material to pass through, especially in river areas that originate at Volcano. The results of the distribution of affected land use and residential areas with a volume of 100 million m3 covering an area of ​​26,815 Ha. The widest distribution is in the rice field area of ​​12,475 Ha, the residential area of ​​6,745 Ha, the garden area of ​​5,264 Ha and the field area of ​​3,330 Ha.